3D culture of murine neural stem cells on decellularized mouse brain sections. (February 2015) - De Waele, Jorrit; Reekmans, Kristien; Daans, Jasmijn; Goossens, Herman; Berneman, Zwi; Ponsaerts, Peter
Abstract: Transplantation of neural stem cells (NSC) in diseased or injured brain tissue is widely studied as a potential treatment for various neurological pathologies. However, effective cell replacement therapy relies on the intrinsic capacity of cellular grafts to overcome hypoxic and/or immunological barriers after transplantation. In this context, it is hypothesized that structural support for grafted NSC will be of utmost importance. With this study, we present a novel decellularization protocol for 1.5 mm thick mouse brain sections, resulting in the generation of acellular three-dimensional (3D) brain sections. Next, the obtained 3D brain sections were seeded with murine NSC expressing both the eGFP and luciferase reporter proteins (NSC-eGFP/Luc). Using real-time bioluminescence imaging, the survival and growth of seeded NSC-eGFP/Luc cells was longitudinally monitored for 1–7 weeks in culture, indicating the ability of the acellular brain sections to support sustained ex vivo growth of NSC. Next, the organization of a 3D maze-like cellular structure was examined using confocal microscopy. Moreover, under mitogenic stimuli (EGF and hFGF-2), most cells in this 3D culture retained their NSC phenotype. Concluding, we here present a novel protocol for decellularization of mouse brain sections, which subsequently support long-term 3D culture of undifferentiated NSC.